Indices of body fat distribution for assessment of lipodysthrophy in people living with HIV/AIDS - Segatto, Aline Francielle Mota [UNESP]; Freitas Junior, Ismael Forte [UNESP]; Santos, Vanessa Ribeiro Dos [UNESP]; Alves, Kelly Cristina de Lima Ramos Pinto; Barbosa, Dulce Aparecida; Filho, Alexandre Martins Portelinha; Monteiro, Henrique Luiz [UNESP] (Springer Nature, 2012)
Background: Metabolic and morphological changes associated with excessive abdominal fat, after the introduction of Antiretroviral Therapy, increase the risk of cardiovascular disease in people living with HIV/AIDS(PLWHA). Accurate methods for body composition analysis are expensive and the use of anthropometric indices is an alternative. However the investigations about this subject in PLWHA are rare, making this research very important for clinical purpose and to advance scientific knowledge. The aim of this study is to correlate results of anthropometric indices of evaluation of body fat distribution with the results obtained by Dual-energy X-Ray Absorptiometry(DEXA) , in people living with HIV/AIDS. Methods. The sample was of 67 PLWHA(39 male and 28 female), aged 43.6+7.9 years. Body mass index, conicity index, waist/hip ratio, waist/height ratio and waist/thigh were calculated. Separated by sex, each index/ratio was plotted in a scatter chart with linear regression fit and their respective Pearson correlation coefficients. Analyses were performed using Prism statistical program and significance was set at 5%. Results: The waist/height ratio presented the highest correlation coefficient, for both male (r=0.80, p<0.001) and female (r=0.87, p <001), while the lowest were in the waist/thigh also for both: male group (r=0.58, p<0.001) and female group (r=0.03, p=0.86). The other indices also showed significant positive correlation with DEXA. Conclusion: Anthropometric indices, especially waist/height ratio may be a good alternative way to be used for evaluating the distribution of fat in the abdominal region of adults living with HIV/ADIS. © 2012 Segatto et al.; licensee BioMed Central Ltd.
Keywords: Abdominal obesity; AIDS/HIV; Body composition; Lipodysthrophy; adipose tissue; adult; body composition; female; human; Human immunodeficiency virus infection; lipodystrophy; male; middle aged; photon absorptiometry; radiography; Absorptiometry, Photon; Adipose Tissue; Adult; Body Composition; Female; HIV Infections; Humans; Lipodystrophy; Male; Middle Aged